2008
DOI: 10.1115/1.2917423
|View full text |Cite
|
Sign up to set email alerts
|

Passive Control Around the Two-Dimensional Square Back Ahmed Body Using Porous Devices

Abstract: The control of two-dimensional flows around the square back Ahmed body is achieved using porous devices added on some parts of the body. The square back Ahmed body is considered either in an open domain or on top of a road. The modelling of the flow in different media is performed by means of the penalisation method. A good choice of the location of the porous interfaces yields a significant improvement of the aerodynamic quantities, specially for the square back body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 21 publications
(27 reference statements)
0
21
0
1
Order By: Relevance
“…Besides, the two-dimensional patterns of vortex shedding from a bluff body have the same qualitative features of the fully developed turbulent phase-averaged results [24]. It may be noted that the previous studies reported on this topic [10][11][12][13] considered certain discrete values of Re in the transitional and turbulent range, and restricted to a two-dimensional analysis. In the turbulent range of Reynolds number, the Darcy-Brinkman model becomes questionable due to the inertial fluctuation of the velocity field in the porous zone.…”
Section: Introductionmentioning
confidence: 57%
“…Besides, the two-dimensional patterns of vortex shedding from a bluff body have the same qualitative features of the fully developed turbulent phase-averaged results [24]. It may be noted that the previous studies reported on this topic [10][11][12][13] considered certain discrete values of Re in the transitional and turbulent range, and restricted to a two-dimensional analysis. In the turbulent range of Reynolds number, the Darcy-Brinkman model becomes questionable due to the inertial fluctuation of the velocity field in the porous zone.…”
Section: Introductionmentioning
confidence: 57%
“…2) with a 1920 Â 640 cells uniform mesh and X = (0, 12) Â (0, 6) Â (0, 4) in three dimensions with a 768 Â 384 Â 256 cells uniform mesh. The grid convergence for the same geometry has been studied in [6] and the grid 960 Â 320 corresponds already to the finest grid required. The velocity vector is U = (u, w) in two dimensions and U = (u, v,w) in three-dimensions.…”
Section: Modelling and Numerical Simulationmentioning
confidence: 99%
“…A control using porous layers is widely studied in [6] for the square back Ahmed body on top of a road. The main difference with the previous study is the distance between the body and the road that is equal to H in [6] and to 0.6H here as in the original benchmark [2].…”
Section: Passive Control Using Porous Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in the car industry the most important aerodynamic parameter is the drag coefficient C D . A large number of simulations,with different porous layer locations,were performed to verify how far this passive control technique can contribute to the drag reduction [11]. In the following,only the most significant results are presented starting with the square back geometry.…”
Section: Control Of the Drag Coefficient Of Ground Vehiclesmentioning
confidence: 99%